Dual left anterior descending artery: diagnostic criteria and novel classification - Jariwala, Pankaj (Indian J Thorac Cardiovasc Surg, 2021)
Duplication of the left anterior descending artery is an uncommon coronary anomaly. Since no proper classification has been established after the initial description and numerical classification by Spindola-Franco et al., many newer numbers have evolved with many overlapping and unclassified variants described in the literature. Identification and reasonable management strategies for dual left anterior descending artery (LAD) are crucial in preventing the long-term disastrous consequences of inadequate revascularization. Clinicians and diagnosticians should be aware of this specific angiographic-based congenital coronary abnormality of the LAD. We, therefore, sought a new, reasonable classification of the dual LAD system, which would clarify this ambiguity, which also has therapeutic implications.